Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1016/j.ejvs.2013.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Automated 2D-3D Image Overlay System Utilizing Subtraction of Bone Marrow Image for EVAR: Feasibility Study

Abstract: "3D Roadmap" was confirmed to be valuable for visualization of vessel origin in a fused image and for reduction of contrast material during EVAR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 20 publications
3
19
1
Order By: Relevance
“…We learned in this study that the deviation in thoracic fusion imaging is greater than in abdominal cases compared with what is reported in the literature 6,8,10,11 and our own unpublished data. Although we assessed the aforementioned clinical failure, we think this high rate of deviation is due to the following difficulties and characteristics of thoracic procedures that change the anatomy or make registration more difficult: (Fig 7).…”
Section: Discussionsupporting
confidence: 50%
“…We learned in this study that the deviation in thoracic fusion imaging is greater than in abdominal cases compared with what is reported in the literature 6,8,10,11 and our own unpublished data. Although we assessed the aforementioned clinical failure, we think this high rate of deviation is due to the following difficulties and characteristics of thoracic procedures that change the anatomy or make registration more difficult: (Fig 7).…”
Section: Discussionsupporting
confidence: 50%
“…Three dimensional (3D) image fusion is an advanced imaging tool that helps the operator, providing useful anatomical information for guidance during endovascular procedures. Several authors have reported their clinical experience with fused imaging during endovascular aortic repair (EVAR), suggesting that the method is feasible 1 and that it can reduce both radiation 2e5 and contrast dose. 6,7 Visualization of anatomical positions derived from pre-operative imaging can be achieved by projecting volume rendered (VR) images or specific marks on the live fluoroscopy screen.…”
Section: Introductionmentioning
confidence: 99%
“…Anand et al [15] introduced a preclinical mobile image overlay system for needle interventions. In vascular surgery, an image overlay system has been used in endovascular aneurysm repair [17]; however, we know of no other reports of using an image overlay system or a tablet PC in peripheral arterial revascularization.…”
Section: Discussionmentioning
confidence: 99%
“…Navigation by augmented reality using image overlay systems has been introduced in several clinical settings, including neurosurgery, orthopedics, urology, and abdominal surgery, and has shown potential utility in assisting the performance of safe and secure surgical or interventional procedures [13][14][15][16][17][18][19][20][21][22][23]. We recently devised a new medical navigation system that superimposes threedimensional (3D) models onto real-time images taken by the back-camera of a tablet personal computer (PC) [24].…”
Section: Introductionmentioning
confidence: 99%